GeoCongress 2012 2012
DOI: 10.1061/9780784412121.438
|View full text |Cite
|
Sign up to set email alerts
|

Load Bearing Capacity of Footing Resting on the Fly Ash Slope with Multilayer Reinforcements

Abstract: In several parts of the world, the disposal of waste materials like fly ash is a challenging task. The applications of fly ash as structural fills in foundations is one of the best solutions to disposal problems, because they can be used in large volumes in such application. There may be difficulty due to poor load-bearing capacity of fly ash, especially when footings rest on the top of the fly ash fill slope; but inclusion of polymeric reinforcements as horizontal sheets within the fill may be advantageous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…EI Sawwaf (2007) reported that reinforcement length (L r ) beyond 5B did not increase the ultimate load of footing significantly. Gill et al (2012) based on the numerical study reported that no significant increase in ultimate bearing capacity was obtained once L r /B ratio reaches to 7.0. Therefore length of the reinforcing layer (L r ) in the present investigation was kept constant and is equal to 7.0B throughout the test programme.…”
Section: Fig 5 Schematic Test Arrangementmentioning
confidence: 96%
See 1 more Smart Citation
“…EI Sawwaf (2007) reported that reinforcement length (L r ) beyond 5B did not increase the ultimate load of footing significantly. Gill et al (2012) based on the numerical study reported that no significant increase in ultimate bearing capacity was obtained once L r /B ratio reaches to 7.0. Therefore length of the reinforcing layer (L r ) in the present investigation was kept constant and is equal to 7.0B throughout the test programme.…”
Section: Fig 5 Schematic Test Arrangementmentioning
confidence: 96%
“…Although several studies have been reported on the behaviour of footing constructed on stabilized sand slopes (Selvadurai and Gnanendran 1989, Huang et al 1994, Lee and Manjunath 2000, Yoo 2001, EI Sawwaf 2007, Alamshahi and Hataf 2009, Mittal et al 2009, but limited studies are available in the literature on load-carrying capacity behaviour of footing resting on reinforced fly ash/coal or pond ash slopes (Choudhary and Verma 2001, Gill et al 2011, 2012. The load-bearing capacity determination technique is an important part for a safe and economical design of footings on reinforced slopes.…”
Section: Introductionmentioning
confidence: 98%
“…Bhardwaj and Mandal [5] presented the study on the behaviour of polypropylene fiber reinforced fly ash slopes. Pointing out the availability of the limited investigations in the literature on load carrying capacity of reinforced fly ash slopes, Choudhary and co-authors [9,19,30] reported experimental, theoretical and numerical studies on the bearing capacity behaviour of strip footing on reinforced fly ash slope. Nadaf and Mandal [40] presented model studies on fly ash slopes reinforced with planer steel grids.…”
Section: Review Of Literaturementioning
confidence: 99%
“…finite difference, finite element, discrete element) have gained popularity in the design practices as they can model several parameters precisely which can not be accounted for in the experimental or theoretical works. There have been few significant studies [1,2,4,5,8,19,20,23,24,28,29,[31][32][33]39] which reported the numerical analysis of the reinforced embankment slope of sand or other types of slopes, [19] and 2013 presented the numerical analysis of the geogrid reinforced fly ash slope in conjunction with the experimental studies. Yet much needs to be investigated with respect to numerical analysis, particularly in the context of the safe and economical design of footings resting on reinforced embankment slopes made up different Pozzolanic waste materials.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This solves the problems associated with the disposal of fly ash. According to two dimensional finite element analysis on reinforced fly ash slope carried by Gill et al(2011) fly ash can be used successfully as an embankment fill material.…”
Section: Introductionmentioning
confidence: 99%